Description of Mothers' Knowledge and Behavior in Preventing Stunting in the First 1000 Days of Life in the Pilolodaa Community Health Center Area - Nurhaliza Ibrahim; Sitti Rahma; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
This study aims to find out the picture of maternal knowledge and behavior in efforts to prevent stunting in 1000 HPK in the working area of the Pilolodaa Health Center. The method used is a quantitative research with a cross-sectional design. The research sample amounted to 92 people who were selected using total sampling. Data collection was carried out using questionnaires that have been tested for validity and reliability. Data were analyzed univariately using SPSS version 27. The results showed that the majority of respondents were in the age range of 26-35 years (47.8%), housewives (88.0%), high school education (45.7%), and had an income below UMP (58.7%). The level of knowledge of mothers in stunting prevention was mostly in the good category, namely 57 respondents (62.0%), followed by the sufficient category of 29 respondents (31.5%) and the category of less than 6 respondents (6.5%). Meanwhile, maternal behavior in stunting prevention was also dominated by the good category of 50 respondents (54.3%), the sufficient category of 33 respondents (35.9%), and the poor category of 9 respondents (9.8%). The conclusion of this study shows that most mothers already have good knowledge and behavior in stunting prevention, but there are still a small number of mothers with less knowledge and behavior, so continuous education and mentoring are needed.